Ego Media - Gee, Lisa (Stanford University Press, 2024)
Enabled by the internet and mobile technologies, digital media have generated profound changes in how and where we communicate, interact, and present ourselves. Ego Media explores the impact of these rapidly evolving media on forms and practices of self-presentation, giving a multidimensional account of how the ego presents itself through and across the digital media landscape, and how this has both changed and remediated earlier modes. Collaboratively written and produced, the project combines a humanistic, life-writing theory approach with an interdisciplinary methodology drawing especially upon digital humanities, cultural theory, sociolinguistics, neurology, and the medical humanities. Genres analyzed range from chatbots to war blogs to mommy vlogs and beyond, offering a breadth of insights into both the aesthetics and the politics of new media. Rather than pursuing each thread of analysis through a single linear narrative, the project is built as a composite picture that mimics the polyphonic nature of social media and is designed to highlight the tensions, contradictions, and coherences that characterize how people use, think, and feel about digital media. Promoting reader agency and keeping the history of autobiographical writing in focus, Ego Media offers a self-referential view of how social media shapes researching and writing about the self.